Long noncoding RNA LINC00339 promotes osteoporosis development via modulating of regulator CDC42 by binding PARP1 - Dong-Li Zhu; Yan Zhang; Xiao-Yu Zhang; Zi-Han Qiu; Ke Li; Xiao-Rong Zhou; Zhen-Zhen He; Xiao-Feng Chen; Shan-Shan Dong; Wen Tian; Ya-Kang Wang; Tie-Lin Yang; et al. (Non-coding RNA Research, 2025)
Background: Osteoporosis is a systemic skeletal disorder characterized by reduced bone mass and microarchitectural deterioration of bone tissue. Our previous investigation provided preliminary evidence that single nucleotide polymorphisms (SNPs) may functionally interact with the LINC00339, potentially contributing to the pathogenesis and progression of osteoporosis through undefined molecular pathways. However, the exact mechanistic basis of LINC00339's involvement in osteoporotic bone remodeling remains incompletely characterized and warrants systematic exploration. Methods: We analyzed the differentially expressed of LINC003339 in different bone tissues by qRT-PCR. ALP and Alizarin red S (ARS) staining were conducted in stably knocked-down and overexpressed of LINC00339 cell lines. RNA fluorescence in situ hybridization (FISH) assays were used to detect the subcellular location of LINC00339. The mechanism of LINC00339 regulating cell division cycle 42 (CDC42) was explored by RNA-protein pull-down, RNA immunoprecipitation (RIP) and Co-IP assays. Results: This study demonstrated significant upregulation of LINC00339 in bone tissue specimens derived from osteoporosis patients compared to healthy controls. Functional analyses revealed that LINC00339 dysregulation exhibited an inverse correlation with osteogenic differentiation capacity across multiple osteoblast cell models. Subcellular localization analysis via FISH confirmed the predominant cytoplasmic distribution of LINC00339 in bone cells. Mechanistically, RNA-protein pull-down assays combined with RNA immunoprecipitation (RIP) identified poly (ADP-Ribose) polymerase 1 (PARP1) as a direct binding partner of LINC00339. Further investigation established that the LINC00339-PARP1 axis cooperatively modulates transcriptional programs critical to bone homeostasis, potentially driving pathogenic mechanisms underlying osteoporosis progression. Notably, integrated transcriptomic and rescue experiments revealed that LINC00339 and PARP1 coregulate CDC42 expression through post-transcriptional regulatory mechanisms. Conclusions: The identification of the LINC00339-PARP1-CDC42 regulatory axis elucidates a novel molecular mechanism contributing to osteoporosis pathogenesis. This discovery not only advances our understanding of epigenetic regulation in bone remodeling but also positions the LINC00339-PARP1 interaction as a potential therapeutic target for modulating osteoblast dysfunction. Importantly, these findings establish a conceptual framework for lncRNA-driven interventions in skeletal disorders, highlighting the translational potential of targeting RNA-protein complexes to restore bone homeostasis.